Do Alu repeats drive the evolution of the primate transcriptome? - Urrutia, Araxi O (BioMed Central, 2008)
BACKGROUND: Of all repetitive elements in the human genome, Alus are unusual in being enriched near to genes that are expressed across a broad range of tissues. This has led to the proposal that Alus might be modifying the expression breadth of neighboring genes, possibly by providing CpG islands, modifying transcription factor binding, or altering chromatin structure. Here we consider whether Alus have increased expression breadth of genes in their vicinity. RESULTS: Contrary to the modification hypothesis, we find that those genes that have always had broad expression are richest in Alus, whereas those that are more likely to have become more broadly expressed have lower enrichment. This finding is consistent with a model in which Alus accumulate near broadly expressed genes but do not affect their expression breadth. Furthermore, this model is consistent with the finding that expression breadth of mouse genes predicts Alu density near their human orthologs. However, Alus were found to be related to some alternative measures of transcription profile divergence, although evidence is contradictory as to whether Alus associate with lowly or highly diverged genes. If Alu have any effect it is not by provision of CpG islands, because they are especially rare near to transcriptional start sites. Previously reported Alu enrichment for genes serving certain cellular functions, suggested to be evidence of functional importance of Alus, appears to be partly a byproduct of the association with broadly expressed genes. CONCLUSION: The abundance of Alu near broadly expressed genes is better explained by their preferential preservation near to housekeeping genes rather than by a modifying effect on expression of genes.